2020
DOI: 10.1177/1098300720946651
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Components and Participant Characteristics Associated With Outcomes in Self-Monitoring Interventions

Abstract: Self-monitoring is one of the most widely used and widely researched strategies for improving student behavior. However, specific research-based guidance about how to design effective self-monitoring interventions and to whom they should be delivered does not yet exist. To this end, we examined how various treatment components and participant characteristics moderated response to self-monitoring interventions. We included 66 single-case studies on academic engagement and 21 single-case studies on disruptive be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
38
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(50 citation statements)
references
References 37 publications
7
38
3
Order By: Relevance
“…No differences were noted for boys compared to girls—though most studies reported SM being applied to boys with challenging classroom behaviors. These findings are similar to those examined in a prior systematic review conducted by Bruhn et al (2020) that noted SM appeared more effective for younger students and for students in special education settings. In practice, behavioral interventions are most often applied to younger students and prior research has suggested these practices are less often applied in middle and high schools (Bruhn et al, 2015; Carter et al, 2011; Mooney et al, 2005; Thompson, 2011; Thompson & Webber, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…No differences were noted for boys compared to girls—though most studies reported SM being applied to boys with challenging classroom behaviors. These findings are similar to those examined in a prior systematic review conducted by Bruhn et al (2020) that noted SM appeared more effective for younger students and for students in special education settings. In practice, behavioral interventions are most often applied to younger students and prior research has suggested these practices are less often applied in middle and high schools (Bruhn et al, 2015; Carter et al, 2011; Mooney et al, 2005; Thompson, 2011; Thompson & Webber, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…Relatedly, given that Jared displayed the greatest behavioral deficits of the three participants, based on his SSIS scores and baseline AE, it is possible that neither intervention was sufficiently intense to change his behavior. Additional components, such as self-evaluation, behavior-specific feedback, or contingent reinforcement, could have made a greater impact, as researchers have found that including feedback or reinforcement in self-monitoring interventions significantly improves AE ( p < .001; Bruhn et al, 2020). Given the empirical evidence supporting these methods of intensifying self-monitoring interventions, Jared may have demonstrated stronger improvements had those components been included.…”
Section: Discussionmentioning
confidence: 99%
“…Future researchers may consider studying the overall effects of a cohesive self-regulation intervention package (goal setting, self-monitoring, self-evaluation, etc.) rather than studying the comparative effects of each strategy individually, as these strategies are often used in tandem (Bruhn et al, 2020). This could build evidence for the overall efficacy of self-directed, packaged self-regulation interventions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations